Relation between monocyte/high density lipoprotein ratio in acute ischemic stroke severity - A., Raveesha; V., Meghashri; R., Vishwanath; K., Prabhakar (International Journal of Research in Medical Sciences, 2020)
Introduction: Stroke is a common neurological condition, with a high incidence of mortality and morbidity, especially in the elderly population. Inflammation and lipid abnormalities have been proposed for the pathophysiology development and progression of atherosclerosis. Monocyte count to High density lipoprotein (HDL) ratio (MHR) is proposed as a novel predictor of prognosis in cardiovascular diseases. In this study, we aim to investigate the relationship of MHR with stroke severity in acute ischemic stroke patients. Methods: A total of 64 patients with acute ischemic stroke were inpatients of RLJH were included in the study. Patients were divided into 2 groups according to the National institute of health stroke (NIHS) score (group 1; national institute of health stroke scale (NIHSS) <16, group 2; NIHSS ≥16). MHR is the ratio obtained by dividing the monocyte count with HDL from a peripheral blood sample. Then the association between MHR and NIHSS score at the time of admission is evaluated. Results: Accordingly, the results obtained revealed MHR was significantly lower in group 1 patients who have lower NIHSS score than group 2 patients who have higher NIHSS. Conclusion: This study suggests that MHR is associated with stroke severity on admission in patients with acute ischemic stroke.